2016
DOI: 10.1088/1751-8113/49/36/369401
|View full text |Cite
|
Sign up to set email alerts
|

Addendum to ‘Algebraic equations for the exceptional eigenspectrum of the generalized Rabi model’

Abstract: In our recent paper (Li and Batchelor 2015 J. Phys. A: Math. Theor. 48 454005) we obtained exceptional points in the eigenspectrum of the generalized Rabi model in terms of a set of algebraic equations. We also gave a proof for the number of roots of the constraint polynomials defining these exceptional solutions as a function of the system parameters and discussed the number of crossing points in the eigenspectrum. This approach however, only covered a subset of all exceptional points in the eigenspectrum. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 11 publications
3
30
0
Order By: Relevance
“…For a discussion of the exceptional spectrum in the case of the original quantum Rabi model, see [35,27]; for a discussion of the exceptional spectrum of a different generalization of the quantum Rabi model, obtained by adding an asymmetric term σ x , see [36,37]. A detailed mathematical symmetry analysis using Lie algebra representations of sl 2 (R) is given for the spectrum of the original quantum Rabi model in [38] and of the asymmetric quantum Rabi model in [39].…”
Section: Numerical Procedures For the Exceptional Spectrummentioning
confidence: 99%
“…For a discussion of the exceptional spectrum in the case of the original quantum Rabi model, see [35,27]; for a discussion of the exceptional spectrum of a different generalization of the quantum Rabi model, obtained by adding an asymmetric term σ x , see [36,37]. A detailed mathematical symmetry analysis using Lie algebra representations of sl 2 (R) is given for the spectrum of the original quantum Rabi model in [38] and of the asymmetric quantum Rabi model in [39].…”
Section: Numerical Procedures For the Exceptional Spectrummentioning
confidence: 99%
“…As pointed out in the Introduction, there are no simple closed-form solutions to the regular spectrum of the QRM. Instead, only the level crossing points in the spectrum can be determined through finite-term constraint polynomials of system parameters [30,31]. For this reason, the QRM is also referred to as quasi-solvable [32][33][34].…”
Section: Exact Solutions For the Exceptional Spectrummentioning
confidence: 99%
“…The other, non-degenerate, set of exceptional points have also been discussed [40,51,86,89,90]. The system parameters do not satisfy a constraint polynomial at these points, but other conditions can be derived.…”
Section: Exceptional Pointsmentioning
confidence: 99%
“…The class of exceptional points not satisfying a constraint polynomial have also been discussed for this model [90]. It has been shown that the effect of the bias parameter ǫ is to induce a conical intersection point in the energy spectrum at each of the two-fold degenerate Judd points located at ǫ = 0 [138].…”
Section: A Generalised Rabi Model Is the Asymmetric Quantum Rabi Modelmentioning
confidence: 99%